IMPLEMENTASI MODEL PEMBELAJARAN CTL BERBANTU APLIKASI GEMAS UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS PESERTA DIDIK - Mira Siti Nur'azizah; Yanti Mulyanti; Hamidah Suryani Lukman (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
This study aims implement a CTL model assisted by the GEMAS application (Educational Mathematics Game for Junior High School) to enhance the mathematical critica thinking skills of students at SMPN 4 Kota Sukabumi. The study employs a quantitative research method with a quasi-eksperimental design and a control gruoup pretest and posttest design. The population of this reseacrh consist of all grade VIII students at SMPN 4 Kota Sukabumi, with samples selected using cluster random sampling technique. The sample includes three classes: VIII E, VIII F, and VIII H, comprising a total of 84 randomly selected students. The reseacrh instruments include four test questions on mathematical critical thinking skills with validated PLSV material, as well as observation sheets. Data analysis was performed using anova with a significance level of 5%. The result indicate that the mathematical critical thinking skills of students using the CTL model assisted by the GEMAS application are better than thse using the CTL model alone, as well as th direct learning model.